2019
DOI: 10.1111/1759-7714.13137
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of artificial pneumothorax with position adjustment for CT‐guided percutaneous transthoracic microwave ablation of small subpleural lung tumors

Abstract: Background To evaluate the efficacy and safety of artificial pneumothorax with position adjustment for computed tomograpy (CT)‐guided percutaneous transthoracic microwave ablation (MWA) of small subpleural lung tumors. Methods Fifty‐six patients with small subpleural lung tumors (< 3.0 cm) entered the study and underwent CT‐guided MWA with (group I: 24 patients with 24 tumors) or without (group II: 32 patients with 34 tumors) the support of artificial pneumothorax. Follow‐up contrast‐enhanced CT scans were rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…After completion of the ablation, the instilled air is removed using the same centesis catheter needle, which is kept in place during the procedure to quickly remove the air if needed. 32 The procedure can be done under sedation or general anesthesia, with preference for general anesthesia in some centers, as it is thought to improve the technique's feasibility, particularly in technically challenging cases where organ displacement or specific patient positioning is required. 20 Under CT guidance, real-time or stepwise according to the operator preference, the microwave applicator (or applicators) is advanced into the lesion.…”
Section: Techniquementioning
confidence: 99%
“…After completion of the ablation, the instilled air is removed using the same centesis catheter needle, which is kept in place during the procedure to quickly remove the air if needed. 32 The procedure can be done under sedation or general anesthesia, with preference for general anesthesia in some centers, as it is thought to improve the technique's feasibility, particularly in technically challenging cases where organ displacement or specific patient positioning is required. 20 Under CT guidance, real-time or stepwise according to the operator preference, the microwave applicator (or applicators) is advanced into the lesion.…”
Section: Techniquementioning
confidence: 99%
“…However, bronchopleural fistula after ablation of the central tumor may not be closed easily by drainage and anti-infective treatment alone, which requires early surgical intervention. On the other hand, previous studies have shown no significant difference in technical success, technical efficacy, local tumor control, and complications with artificial pneumothorax compared with no artificial pneumothorax (32). Although studies have shown that artificial air/hydrothorax can reduce pain in patients (33), it does not reduce the occurrence of bronchopleural fistula.…”
Section: Discussionmentioning
confidence: 91%
“…All patients were evaluated before, during, and after the MWA procedure using a visual analog scale (VAS) system, which was applied in previous literature (16)(17)(18). The patients were scored and recorded on the VAS scale before, during, and 24 hours after the procedure to compare the differences in pain degrees between the two groups.…”
Section: Pain Assessmentmentioning
confidence: 99%